Innovation, Inequality and a Golden Rule for Growth in an Economy with Cobb-Douglas Function and an R&D Sector - Paul J. J. Welfens (Institute for the Study of Labor (IZA), 2015)
The innovative approach presented introduces a modified neoclassical growth model which includes a new bias of technological progress in a quasi-endogenous growth model in which part of labor is used in the research & development sector. The combination of a macroeconomic production function and a new progress function, plus the assumption that the output elasticity of capital is positively influenced by the size of the R&D sector, sheds new light on innovation and growth as well as income inequality: Thus there is a new approach for explaining Piketty's historical findings of a medium term rise of the capital income share in industrialized countries both in the earlier and later part of the 19th century and in 1990-2010. A rising share of capital income can be explained within this approach by the increase in the output elasticity of capital, which has been developed in a new way, namely in the context of R&D. In the approach presented herein, the golden rule issues are also highlighted and it is shown that choosing the right size of the R&D sector will bring about maximum sustainable per capita consumption. While the basic new model is presented for the case of a closed economy, one could easily accommodate both trade and foreign direct investment and thereby get a better understanding of complex international investment, trade and FDI dynamics including with respect to the envisaged Transatlantic Trade and Investment Partnership.
Keywords: O11; O32; O40; D63; 330; innovation; growth; inequality; golden rule; Piketty